Mood Disorder Due to a General Medical Condition with Manic Features - J. P. Oliveira; S. L. Morais; D. Araújo; C. G. Carlotti; B. O. Colli; J. A. S. Crippa; J. E. Cecílio Hallak (Case Reports in Medicine, 2009)
This case report describes a patient with manic and psychotic symptoms who had a history of neurocysticercosis and presented with an episode of hypertensive hydrocephalus in 2003. Despite her history, she was initially treated for primary psychiatric disease.